Metal Music as a Medium of Da'wah Communication (Album 7:172 Band Purgatory) - Dhista Almayda*, Sabian Ray; Zulfiningrum, Rahmawati (Riwayat: Educational Journal of History and Humanities, 2023)
Purgatory is a metal band from Jakarta that creates Music that contains a Message of da'wah in it. Purgatory released an album entitled "7:172" which describes describes the meaning of letters and verses in the holy book of the Quran. Some of the songs On the album have lyrics and diction that contain elements of Da'wah or conveying the teachings of the Islamic religion to the listener in a wise Way. This study Aims to find Out how the Communication effect of the album "7:172" Purgatory axle a medium of Communication for proselytizing. The Research uses a qualitative descriptive approach, Music Communication theory as the play theory and Da'wah Communication theory axle a Support axle Well axle Ferdinand De Saussure's Semiotic method. Data Collection techniques include observation, in-depth interviews, and documentation. The results showed that the Communication effect of several songs On the album "7:172" Purgatory discusses human Nature and Bad behavior, the importance of Modeling the Prophet Muhammad SAW, Criticism of those Who Want to Divide the Islamic ummah, and also the Feelings of a Person Who experiences regret for the Sins he tenderloin committed.